Is the somatotropic axis related to sympathetic nerve activity in healthy ageing men? - Sverrisdóttir, Y; Johannsson, G; Jungersten, L; Wallin, BG; Elam, M (2001)
OBJECTIVE: The mechanisms underlying the age-related increase in blood pressure and sympathetic nerve activity remain largely unknown. The decline in growth hormone (GH) secretion and insulin-like growth factor-I (IGF-I) with age has been related to several cardiovascular risk factors. Low serum IGF-I levels in severe adult GH deficiency is associated with markedly increased sympathetic nerve activity. This study evaluates whether a relationship between serum IGF-I and sympathetic nerve traffic exists in healthy aging men. DESIGN AND METHODS: Sympathetic nerve activity to the muscle vascular bed (MSA) was recorded in 56 healthy normotensive males, and related to age (range 21-71 years), body mass index (BMI, range 18.4-32.2), serum IGF-I and plasma nitrate levels. Blood pressure, BMI and MSA increased with age, whereas IGF-I and plasma nitrate decreased. In a forward stepwise multiple regression analysis, age explained 40% of the variability in MSA and excluded other variables. Omitting age, IGF-I became the strongest independent predictor, explaining 23% of the variability in MSA. MSA was an independent predictor of diastolic blood pressure, but its influence (10%) was less than that of BMI (28%). BMI was not related to MSA or IGF-I. CONCLUSIONS: Decreased serum IGF-I levels are coupled to increased MSA during ageing, an effect independent from the impact of increased body weight. Although MSA is a weak predictor of rising blood pressure with age, it constitutes one possible pathway for the somatotropic axis to affect cardiovascular function in ageing.